2007
DOI: 10.1507/endocrj.k06-162
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics Influencing the Effectiveness of Metformin on Japanese Type 2 Diabetes Receiving Sulfonylureas

Abstract: Abstract. In this study, we described the effectiveness of metformin on Japanese type 2 diabetes patients receiving sulfonylureas and the clinical characteristics of the patients whose glycemic control were significantly improved with metformin administration. Our results showed that the reduction of glycohemoglobin (HbA 1C ), serum concentration of total cholesterol, and diastolic blood pressure was statistically significant through the administration of metformin. The clinical characteristics of the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…There was no significant relationship between the rate of decrease in HbA1c and baseline BMI or HOMA2-IR indicating insulin resistance, which was similar to that reported in Asian studies [22,[34][35][36]. This drug is widely used in patients with T2D, who are mainly obese and insulin-resistant.…”
Section: Effect Of Metformin In Patients With Decreased Insulin Secre...supporting
confidence: 84%
“…There was no significant relationship between the rate of decrease in HbA1c and baseline BMI or HOMA2-IR indicating insulin resistance, which was similar to that reported in Asian studies [22,[34][35][36]. This drug is widely used in patients with T2D, who are mainly obese and insulin-resistant.…”
Section: Effect Of Metformin In Patients With Decreased Insulin Secre...supporting
confidence: 84%
“…But we also know that there are nonresponders to any drug. Numerous post hoc studies have revealed some predictors of better responses, but the data are inconclusive (57–60). Furthermore, those response differences tend to be small, and the strongest predictor remains baseline A1C, with the patients with higher A1C levels responding with greater reductions although not necessarily attaining target levels (58,61).…”
Section: State Of the Art For Personalizing Medicinementioning
confidence: 99%